Differences in the use of coping strategies among boys and girls of secondary schools in the Olomouc Region - Zouharová, Martina; Plevová, Irena; Chrásková, Marie (e-Pedagogium, 2019)
The submitted article considers coping strategies that are used to handle any burden or difficult life situation. The main aim of the study was to find out whether there are significant differences in choosing coping strategies among boys and girls during adolescence. A standardized SVF 78 questionnaire was used to collect data (Janke et al., 2003). The questionnaire was used to distinguish ways of dealing with stress, diagnosing positive and negative coping strategies. The research group consisted of students of secondary schools in the Olomouc region, a total of 155 pupils: 73 girls (47%) and 82 (53%) boys. The statistical processing of the results shows more frequent selection of positive coping strategies among boys.
Keywords: Key words: adolescent; school; stress; coping.